2022
DOI: 10.3390/agronomy12112737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar on the Growth, Photosynthesis, Antioxidant System and Cadmium Content of Mentha piperita ‘Chocolate’ and Mentha spicata in Cadmium-Contaminated Soil

Abstract: Cadmium (Cd) is a common heavy metal contaminant which seriously affects plant growth and environmental safety. Biochar, as an organic soil amendment, has been shown to effectively mitigate Cd damage to plants. To study the effectiveness of biochar on mitigating Cd stress, Mentha piperita ‘chocolate’ and Mentha spicata were used in a pot experiment of Cd stress with a CdCl2 solution (10 mg Kg−1), while a biochar suspension (0, 40, 80, and 160 g Kg−1) was applied to the soil. The effects of Cd on the growth, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Dadasoglu et al (2022) observed that Cd stress led to a decrease in seedling height and leaf area of the bean, whereas the biochar treatment could effectively increase plant height and leaf area in Cd-stressed bean plants. Further, the positive effects of biochar on plant growth performance under Cd contamination was similarly obtained in studies on wheat (Ali et al, 2019) and mint species (Jiang et al, 2022).…”
Section: Effects Of Wood Biochar On Plant Height Leaf Area and Leaf N...mentioning
confidence: 61%
“…Dadasoglu et al (2022) observed that Cd stress led to a decrease in seedling height and leaf area of the bean, whereas the biochar treatment could effectively increase plant height and leaf area in Cd-stressed bean plants. Further, the positive effects of biochar on plant growth performance under Cd contamination was similarly obtained in studies on wheat (Ali et al, 2019) and mint species (Jiang et al, 2022).…”
Section: Effects Of Wood Biochar On Plant Height Leaf Area and Leaf N...mentioning
confidence: 61%
“…Recent research has shown that biochar is a cost-effective and environmentally friendly additive for stabilizing and remediating heavy metal-contaminated soils ( Yang L. et al, 2020 ; Yang Y. W. et al, 2020 ; Sun et al, 2022 ). A mixture of biochar and organic fertilizer can effectively address issues of soil heavy metal pollution, nutrient imbalance, and growth inhibition of Mentha crispa L. ( Jiang et al, 2022 ; Ghassemi and Farhangi, 2023 ), purslane ( Han et al, 2022 ), alfalfa ( Kareem et al, 2022 ), and rapeseed ( Zhang C. et al, 2023 ; Zhang N. H. et al, 2023 ; Zhang X. et al, 2023 ; Zhang Z. et al, 2023 ; Zhang K. et al, 2023 ). We also found that the mixed application of biochar and organic fertilizer reduced both TCd in Sophora fields and Cd content in Sophora ( Figures 1A , H ; Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by [5] showed that giving rice husk biochar was able to increase plant height, leaf length, and leaf width of the mint. Previous research by [6] by giving LOF paitan can increase the number of leaves, number of branches, fresh weight of plants, and dry weight of mint plants (Mentha arvensis L.).…”
Section: Introductionmentioning
confidence: 97%